Potensi Keberlanjutan Kewirausahaan Gatra Kreatif - Ibrahim, Irma; Ati, Sarmina (Peneliti.net, 2025)
Currently, the number of unemployed with a bachelor's degree in Indonesia is still increasing, this illustrates that the absorption of the labor market with college graduates is currently still low. To balance this, there needs to be an effort to foster an entrepreneurial spirit among students, in order to reduce educated unemployment in this country. The government has made many efforts to intensify the entrepreneurial spirit among students, one of which is by providing a forum for students to create entrepreneurial groups. Akbid Cahwala North Maluku has an entrepreneurial group called Gatra Kretaif. Gatra Kretaif has more than thirty products. This study aims to describe the entrepreneurial potential of the Gatra Kretaif student group. The research approach used in this study is a qualitative approach. This research was conducted at Akbid Cahwala North Maluku. The subjects of the study consisted of the Gatra Kreatif student entrepreneurial group totaling 30 students. The research instruments were interview guidelines, observation sheets, questionnaires, and recording devices (cellphone cameras). The data in this study consisted of primary and secondary data. Primary data in the form of interview results, observation results, and questionnaire results, then primary data in the form of documentation results of activities related to the production and marketing of creative gatra entrepreneurship products. The steps for analyzing data include data reduction, data presentation, and the conclusion stage. The results of the study indicate that the creative gatra student entrepreneurship group has the potential to become entrepreneurs, and has great opportunities in continuing the business.